Geophysical methods for detecting shallow sulphide mineralization in the Halifax Formation, Nova Scotia: a reconnaissance study - Howells, Ken; Fox, D. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1998)
Construction activities have exposed sulphide-bearing slates of the Halifax Formation in southern mainland Nova Scotia. Under atmospheric conditions the sulphides break down and cause acid rock drainage (ARD) which adversely affects local ecosystems. These effects have been a major problem at the Halifax International Airport, causing fish kills and the expenditure of millions of dollars to ameliorate the ARD. A preferable alternative is to locate areas of sulphide mineralization in the construction area prior to excavation. Concentrated zones of sulphide mineralization can then be avoided, or treatment plans can be formulated in advance. Geophysical surveys provide possible means of detecting sulphides in slates of the Halifax Formation. To evaluate various geophysical methods, reconnaissance profiles were carried out in two areas near the Halifax International Airport utilizing ground conductivity, magnetic, VLF EM, spontaneous potential, and induced polarization measurements. The conductivity meter selected was specific to "construction depths" (i.e., its exploration depth limit is 6 m or less). Test pits were dug on one line in each area to sample bedrock coincident with and between conductivity anomalies. Bedrock samples collected in each test pit were analyzed for total sulphur, total carbon, Fe*\ and Fe3* contents. On the first grid, increased total sulphur content was measured in rock specimens from a test pit coincident with a large ground conductivity anomaly. In contrast, extremely small total sulphur content was measured in rock specimens from a nearby hole which was deliberately situated where there is no conductivity anomaly. Similar results were obtained from the second grid. Magnetic anomalies are coincident with all but one of the sampled conductivity anomalies, indicative of the presence of pyrrhotite. Combined ground conductivity, magnetic and VLF EM surveys appear to be a practicable method for detecting near-surface sulphide mineralization in the Halifax Formation, and such surveys should be included in the Nova Scotia Environment Act.